Attitudes and preferences of the homeowners who renovated their house towards timber as a building material in Bachok, Kelantan - Ab Aziz, Nur Aiman Shuhada (2018)
Peninsular Malaysia has been fortunate to be endowed with extensive areas of valuable natural tropical rainforest which are extremely complex ecosystems are richer in tree species, than in similar areas of Africa and South America. The major consumer of timber and timber products in the domestic market is the construction industry. Timber is a versatile and durable material which found its usage in various aspects of people’s lives for thousands of years. Timber usages are well-known for their broad ranges of uses for society, for example, as a material for the construction of buildings. However, it is claimed that the demand and usage of wood among domestics are decreasing over the years. This study analysed homeowners’ attitudes and preferences